Pharmacogenetic educational needs and the role of pharmacogenetics in primary care: a focus group study with multiple perspectives - Ferwerda, Maaike E.; Wright, Jessica A.; El Melik, Razan M.; Swen, Jesse J.; Houwink, Elisa J. (Frontiers in Pharmacology, 2024)
In this research we explored the attitudes, knowledge, barriers, skills needed and preferred educational program needed to optimize the educational strategies of pharmacogenomics for Family Medicine clinicians. We think our manuscript would fit beautifully within the scope of the special issue "State of the Science of Pharmacogenomics Implementation in Healthcare Systems and Communities", as we can only implement pharmacogenomics better if our clinicians are educated and interested in using pharmacogenomics. By tailoring this education to their needs, the education will be useful and not a waste of time and resources. In our study we identified four themes: (1) need for PGx competences, (2) insight into the roles and responsibilities of PGx services, (3) optimization of PGx workflow through artificial intelligence integrated in the electronic health record, and (4) the ethical dilemmas and psychological effects related to PGx. By addressing these themes, and with further research the most fitting educational program can be created, aiding in the implementation of pharmacogenomics (in family medicine/primary care practice).